Daily Activity Measures and Milk Yield Immediately Before and After a Fertile Estrus - J. S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 2022)
The objective was to characterize changes in milk yield and other physical measures during a 7-day periestrual period encompassing estrus (day 0) and insemination. Lactating dairy cows milked thrice daily were fitted with CowManager SensOor ear tags capable of assessing real time eating, rumination, resting, high activity (estrus), ear-surface temperature, and providing heat alerts. Daily milk was unchanged during the periestrual period. Daily ear-surface temperature was greater during days 1 to 3 compared with day 0. Daily rumination and resting times reached nadirs on day 0, with decreases occurring 48 hours before estrus. Both rumination and resting times increased by 25 or 81% on the day after estrus, respectively. In contrast, daily eating time was greatest on the day of estrus compared with 3 days before and after estrus. High activity increased by 97% during 48 hours before estrus, peaked at estrus, and then decreased to a constant level during days 1 through 3. In conclusion, resting and rumination activity decreased to daily nadirs while eating and high activity peaked on the day of estrus. Fertile estrus was associated with 12% greater high activity, 11% less resting time, and 6% less rumination time.
Keywords: eating; estrus; resting; rumination